Towards extractive justice: Europe, Africa and the pressures of resource dependency. Issue 2 (3rd April 2019) - Mostert, Hanri; Young, Cheri-Leigh; Hassman, Julie L
ABSTRACT: The relationship between Europe and Africa, in the context of the extractives sector, is multi-faceted, influenced by historical, political, social, environmental, geographical, religious and cultural factors. It is the premise of this article that Africa can benefit more fully from its mineral resources, and Europe from its investments into minerals and energy in Africa, if strong capacity is developed to create and implement more sound legal frameworks and better governance in the extractives sector. This contribution explores the historical and current asymmetries in resource interdependency between the two continents, as well as the policy tools that must direct future development of the intercontinental relationship in as far as the extractive sector is involved. The article then proposes three ideas about justice key to building a theory of resource interdependency, pointing to three areas that will require further scholarly engagement in imagining a new future relationship between Europe and Africa.